(untitled) (Indian Journal of Animal Production and Management, 2016)
The aim of this study was to evaluate the effect of different floor space on rumination and resting behaviour of Osmanabadi kids. Eighteen Osmanabadi castrated kids with an initial average body weight (BW) of 6.80 kg at 3-4 months old age (after weaning) were used in this experiment. There were three different floor space provision of 0.8, 0.7 and 0.6m2 in three experimental groups (T0, T1 and T2 respectively) with the same managemental conditions. The behaviours were observed using continuous focal sampling method and measured as minutes/4hr/week. The results indicated that the lying period under the category of resting behaviour and rumination duration were significantly (P<0.05) higher with increasing floor space, In conclusion, floor space provision as managerial practice in goats has effects on resting and rumination behaviour, where more floor space is favourable to the goats.